The status and conservation of shallow - water coastal ecosystem in Malaysia - Charles, Joseph K. (Malaysian Society of Marine Science, 1982)
Although covering an area of only 650,000 hectares {or about 3% of Malaysia's total land area} the mangroves are extremely productive and may playa vital role in supporting the adjacent coastal fisheries. Mangroves are being reclaimed or extripated for various alternate uses at an alarming rate, e.g. 20% being lost over the last 20 years in Peninsular Malaysia. It is proposed that about 5,000 hectares of Malaysia's mangroves {less than 1% the total mangrove area} be set aside for posterity {perpetuation of genetic material, scientific research, education, etc.} as National Parks. The rest of the mangroves should be managed on a sustained yield basis {as done at the Matang Mangrove Forest Reserve} until such time as we have a better understanding of the processes and functioning of this ecosystem. We do not have answers to many very basic and vital {for rational management} questions regarding our mangroves {e.g. How significantly does the mangrove ecosystem contribute to the coastal fisheries?}. There has been practically no research done on the mangrove ecosystem in the past. Even now, too little is being done. An appeal is made {particularly to our research institutes and institutes of higher learning} for a concerted effort on mangrove research. Unless some basic research is done concertedly and with urgency, we may be left with no mangrove to talk about.